When less is more: Innovations for tracking progress toward global targets - Rosenstock, Todd S.; Lamanna, Christine; Chesterman, Sabrina; Hammond, James; Kadiyala, Suneetha; Luedeling, Eike; Shepherd, Keith D.; DeRenzi, Brian; Wijk, Mark T. van (Elsevier, 2017)
Accountability and adaptive management of recent global agreements such as the Sustainable Development Goals and Paris Climate Agreement, will in part rely on the ability to track progress toward the social and environmental targets they set. Current metrics and monitoring systems, however, are not yet up to the task. We argue that there is an imperative to consider principles of coherence (what to measure), standardization (how to measure) and decision-relevance (why to measure) when designing monitoring schemes if they are to be practical and useful. New approaches that have the potential to match the necessary scale of monitoring, with sufficient accuracy and at reasonable cost, are emerging; although, they represent a significant departure from the historical norm in some cases. Iterative review and adaptation of analytical approaches and available technology will certainly be needed to continuously design ways to best track our progress.